Characterization of a Novel Acyl-ACP Δ9 Desaturase Gene Responsible for Palmitoleic Acid Accumulation in a Diatom Phaeodactylum tricornutum - Liu, Baoling; Sun, Yan; Hang, Wei; Wang, Xiaodan; Xue, Jinai; Ma, Ruiyan; Jia, Xiaoyun; Li, Runzhi (Frontiers in Microbiology, 2020)
Palmitoleic acid (16:1Δ9) possesses a double bond at the seventh carbon atom from methyl end of the acyl chain and belongs to unusual ω-7 monounsaturated fatty acids with broad applications in food, pharmaceuticals, cosmetics, biofuel and other industries. This high-value fatty acid accumulates up to >40% of total lipid in the marine diatom Phaeodactylum tricornutum. The present study was conducted to determine the key gene responsible for 16:1Δ9 biosynthesis in this unicellular alga. A new full-length cDNA and genomic DNA encoding acyl-ACP Δ9 desaturase (PtAAD) were isolated from P. tricornutum cells. Expression levels of PtAAD gene under normal and stress culture conditions were both positively correlated with 16:1Δ9 accumulation, implying its potential role for fatty acid determination. Functional complementation assay of a yeast mutant strain BY4839 evidenced that PtAAD could restore the synthesis of unsaturated fatty acid (UFA), especially generating high levels of 16:1Δ9. Further transient expression of PtAAD gene in Nicotiana benthamiana leaves was accompanied by the accumulation of 16:1Δ9, which was absent from control groups. Three-dimensional structure modeling studies showed that functional domain of PtAAD contained three variant amino acids (F160, A223 and L156), which may narrow the space shape of substrate-binding cavity to ensure the entry of 16:0-ACP. Consistent with this prediction, the mutated version of PtAAD gene (F160L, A223T and L156M) in N. benthamiana systems failed to accumulate 16:1Δ9, but increased levels of 18:1Δ9. Taken together, PtAAD exhibits a strong enzymatic activity and substrate preference for 16:0-ACP, acting as the key player for high biosynthesis and accumulation of 16:1Δ9 in this alga. These findings provide new insights for better understanding palmitoleic acid and oil biosynthetic mechanism in P. tricornutum, indicating that PtAAD gene may have practical applications for enriching palmitoleic acid and oil yield in other commercial oleaginous algae and crops.